The food in jars kitchen : 140 ways to cook, bake, plate, and share your homemade pantry - McClellan, Marisa (Running Press, 2019)
Marisa McClellan wants everyone to know that a pantry full of homemade jams, jellies, salsas, and pickles can do a whole lot more than accompany toast. They can add bold bursts of flavor to your home cooking! In her fourth book, she provides 140 recipes for incorporating preserves into everyday dishes. It is as simple as stirring applesauce into a dish of baked oatmeal, brushing apricot jam onto a whole chicken, or building your pasta salad with a jar of pickled vegetables.